Hotel room cleaning: Time study and analysis of influential variables in a Spanish hotel - Victor G. Aguilar-Escobar; Pedro Garrido-Vega; Julián Majado-Márquez; José-Antonio Camu\~nez-Ruiz (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Housekeeping is an important hotel process from the point-of-view of the number of work hours it takes and its impact on customer satisfaction. However, few previous scientific studies have addressed this topic or the variables that are determinants of the time required to clean a room. Design/methodology/approach: A stopwatch Time Study has been performed in a 4-star-hotel. Additionally, data on several variables that could affect cleaning time have been collected and subjected to regression analysis. Findings: Results show that only the task-related variables have a statistically significant influence on total cleaning time. None of the analyzed employee-related variables have any effect on cleaning time. Moreover, five tasks represent over 2/3 of the total cleaning time. Originality/value: In addition to empirically identifying the variables that influence cleaning time and to what extent, this study demonstrates the advantages of using stopwatch time studies to establish cleaning times.
Keywords: 650; Hotel management; housekeeping; room cleaning; time study; regression analysis